Non-rhabdomyosarcoma soft tissue sarcoma in a neonate, a rare and aggressive disease: case report - Khanna, Tanvi; Das, Kunal; Kalra, B. P. (International Journal of Contemporary Pediatrics, 2018)
Neonatal soft tissue sarcomas are a rare group of tumors. The behavior and aggressiveness of neonatal STS is variable. Surgical excision has been noted to be most important factor affecting outcome. However, when non-mutilating surgery is not possible, or resection is incomplete, chemotherapy and radiotherapy have been tried with variable success. We encountered a case of a neonate having large soft tissue mass at anterior abdominal wall. Biopsy and immunohistochemistry confirmed it as undifferentiated soft tissue sarcoma. Surgical excision was incomplete with margin positivity. His disease showed recurrence in short duration of time and despite adjuvant chemotherapy, progression was noted. The child abandoned the treatment and died within 3 months of life.